Adolescent experiences and adult work outcomes - Greve, Henrich R.; Seidel, Marc-David L. (Research in the sociology of work ;, 2014)
This volume of Research in the Sociology of Work starts with a deceptively simple question of, "Do events and experiences during adolescence influence the work outcomes of individuals when they reach adulthood?" While at first glance simple, the question has a wide range of theoretical and practical implications, which are covered in a compelling set of contributions. The volume contains new and exploratory research related to this fundamental question and highlights the opportunities for further research on the topic.